Comparison of economic systems : theoretical and methodological approaches - Eckstein, Alexander (Berkeley : University of California Press, 1971)
The book is the product of a conference on the scope, method, and theory of comparative economic systems, held at the University of Michigan in November 1968; the contributions are uniformly good. An attempt is made to break out of what Eckstein calls the "ismistic" study of comparative systems based on the traditional "isms" such as capitalism, socialism, and fascism. The symposium is therefore primarily methodological. The objectives of the symposium seem eminently desirable. Comparative economics needs to get away from merely odious comparisons and a simplistic study of "isms" and to abstract polarized models into a realistic and descriptive framework, not only of the multidimensional spectrum of economic institutions, but also the multidimensional spectrum of criteria for appraisal. Perhaps the most significant idea in the symposium is the need for what might be called functional comparisons, which will break down the similarities and differences among different systems by sectors of the economy and by institution.
Revision of the papers presented at the conference held Nov., 1968 at the University of Michigan.
Includes bibliographical references and index.
rpm 01/11/2017
Loans
Keywords: Comparative economics